Theoretical and Practical Aspect of Employees and Their Activity Evaluation Model (In Example of Statutory Institution) - Ruta Adamoniene; Jolanta Solnyskiniene; Lina Rupeikiene (Institute of Economic Research (IER), 2017)
The evaluation of employees and their activity requires precise and responsible preparation, it is a process, having a large impact to successful implementation of strategic goals of institution. The evaluation of official work of civil servants in Lithuania does not have deep traditions. Thus, the main analyzed problem is the following: if the criteria of statutory institution employees and their activity evaluation (possibilities and results) are significant to the evaluation results of statutory institution employees and their activity. To make the analysis of theoretical aspects of employees and their activity evaluation and to provide an evaluation improvement model of statutory institution employees and their activity. While analyzing the theoretical peculiarities of employees and their activity evaluation, the analysis, systematization and generalization of scientific literature, scientific articles as well as legislation of the Republic of Lithuania acts have been performed. A quantitative research method was used for the performance of the empiric research; and the qualitative content analysis, descriptive statistical data analysis as well as comparative analysis were used for the analysis of the gathered data. The used in this part researches methodology and results combine the identification of interconnection of statutory institution employees and their activity evaluation possibilities (leadership, people and processes) as well as measuring of their importance. Seeking for useful and effective employees and their activity evaluation process in a statutory institution, a theoretical model of employees and their activity evaluation in a statutory institution improvement was developed on the basis of general evaluation model, which has been successfully adapted in a statutory institution. Having identified the problematic fields of employees and their activity evaluation and determined the reasons of their occurrence and possible improvement opportunities, on the basis of the obtained results, a model of statutory institution employees and their activity evaluation improvement with the indicated in a research problematic fields, improvement possibilities and expected positive results is provided.
Keywords: M12; 330; employees; employees and their activity evaluation; evaluation model